Gonadotropin-Releasing Hormone Receptor-Targeted Near-Infrared Fluorescence Probe for Specific Recognition and Localization of Peritoneal Metastases of Ovarian Cancer - Liu, Qiyu; Zhou, Xiaobo; Feng, Wei; Pu, Tao; Li, Xiaoping; Li, Fuyou; Kang, Yu; Zhang, Xiaoyan; Xu, Congjian (Frontiers in Oncology, 2020)
Background: Peritoneal dissemination is common in advanced ovarian cancer. The completeness of cytoreduction is an independent prognostic factor. The intraoperative fluorescence imaging via tumor-specific near-infrared fluorophore might improve staging and surgical completeness. A promising target for ovarian cancer is the gonadotropin-releasing hormone receptor (GnRHR). This study aimed to develop a GnRHR-targeted near-infrared imaging probe for the detection of peritoneal metastases of ovarian cancer. Methods: Indocyanine green (ICG) was conjugated with GnRH antagonist peptide to develop an ovarian cancer-selective fluorescence probe GnRHa-ICG. GnRHR expression was detected in ovarian cancer tissues. The binding capacity of GnRHa-ICG and ICG was detected in both cancer cell lines and mouse models of peritoneal metastatic ovarian cancer using fluorescence microscopy, flow cytometry, and near-infrared fluorescence imaging. Results: Tissue microarray analysis revealed the overexpression of GnRHR in ovarian cancer. GnRH-ICG exhibited the binding capacity in a panel of cancer cell lines with different expression levels of GnRHR. In ovarian cancer mouse models, GnRHa-ICG signals were detected in peritoneal tumor lesions rather than normal peritoneal and intestines tissues. ICG showed intensive fluorescence signals in intestines. The tumor-to-muscle ratio and tumor-to-intestine ratio of GnRHa-ICG was 7.41 ± 2.82 and 4.37 ± 1.66, higher than that of ICG (4.60 ± 0.50 and 0.57 ± 0.06) at 2 h post administration. The fluorescence signal of peritoneal metastases peaked in intensity at 2 h and maintained for up to 48 h. ICG also showed a weak signal in the tumor lesions due to the enhanced permeability and retention effect, but the intensity decreased quickly within 48 h. Conclusions: The developed GnRHR-targeted imaging agent GnRHa-ICG could specifically detected peritoneal tumor lesions from normal peritoneal and intestines tissues because of the modification of GnRHa to ICG. The plateau period of GnRHa-ICG accumulation may be feasible for clinical applications in fluorescence-guided surgery. Our GnRHR imaging concept may be effective in other hormone-related tumors with upregulated GnRHR expression.